2020
DOI: 10.3390/ma13183922
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder-Bed Fusion as an Alloy Development Tool: Parameter Selection for In-Situ Alloying Using Elemental Powders

Abstract: The design of advanced alloys specifically tailored to additive manufacturing processes is a research field that is attracting ever-increasing attention. Laser powder-bed fusion (LPBF) commonly uses pre-alloyed, fine powders (diameter usually 15–45 µm) to produce fully dense metallic parts. The availability of such fine, pre-alloyed powders reduces the iteration speed of alloy development for LPBF and renders it quite costly. Here, we overcome these drawbacks by performing in-situ alloying in LPBF starting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 53 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…This is especially true if the melting point of the added elements is far above the melting point of the main alloying element. Aota et al [14] investigated in-situ alloy formation of 1.4307 (AISI 304L) from elemental Fe, Ni and Cr powder. They achieved a homogeneous element distribution for certain parameter combinations and concluded that the dwell time of the particles in the meltpool is crucial for achieving a complete dissolution of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true if the melting point of the added elements is far above the melting point of the main alloying element. Aota et al [14] investigated in-situ alloy formation of 1.4307 (AISI 304L) from elemental Fe, Ni and Cr powder. They achieved a homogeneous element distribution for certain parameter combinations and concluded that the dwell time of the particles in the meltpool is crucial for achieving a complete dissolution of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…To date, aluminium alloys have attracted wide interest thanks to their excellent strength-to-weight ratio, but their considerable solidification shrinkage, tendency to oxidation, high laser reflectivity and the poor flowability of their powders make these alloys challenging to process by PBF-LBM [6][7][8]. Considering the non-printability by PBF-LBM of some of the traditional high-strength Al alloys, the challenge of creating new tailored compositions is still ongoing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mixing, blending and in-situ alloying for the production of adapted alloys have already been presented for LAM for different materials [9], such as high entropy alloys (HEAs) [8,[10][11][12], aluminum alloys [13][14][15][16][17][18], titanium [19][20][21][22] or stainless steels [23], but also for different LAM technologies [15,24,25]. Studies on wear-resistant Fe-based alloys are rarely found [9,26].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that even some elemental powders, such as Ni [27], which have a similar melting temperature compared to Fe, can be dissolved during LAM. In contrast, higher melting elements, such as Cr or W, can hardly be dissolved in the melt pool [12,17,23,26]. The incomplete melting of raw material particles results in non-uniform chemical compositions as well as in high porosity [15,20,25,28].…”
Section: Introductionmentioning
confidence: 99%